2004
DOI: 10.1212/01.wnl.0000118202.19098.10
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of STN impairs aspects of cognitive control in PD

Abstract: STN stimulation reduces working memory and response inhibition performance under conditions of greater challenge to cognitive control despite significant improvement of motor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(118 citation statements)
references
References 44 publications
13
101
2
1
Order By: Relevance
“…Simulated STN lesions led to premature responding and impaired high-conflict decisions. This is consistent with observations that lesions of the STN in rodents produce premature responding (Baunez et al, 2001;Desbonnet et al, 2004) and that deep-brain stimulation of the STN can impair cognitive control (Hershey et al, 2004). A recent study shows that stimulating the STN interferes with patients' ability to modulate their RTs by the degree of response conflict, thereby causing impulsive behavior (M. J. Frank, J. Samanta, and S. J. Sherman, unpublished observation).…”
Section: Discussionsupporting
confidence: 88%
“…Simulated STN lesions led to premature responding and impaired high-conflict decisions. This is consistent with observations that lesions of the STN in rodents produce premature responding (Baunez et al, 2001;Desbonnet et al, 2004) and that deep-brain stimulation of the STN can impair cognitive control (Hershey et al, 2004). A recent study shows that stimulating the STN interferes with patients' ability to modulate their RTs by the degree of response conflict, thereby causing impulsive behavior (M. J. Frank, J. Samanta, and S. J. Sherman, unpublished observation).…”
Section: Discussionsupporting
confidence: 88%
“…DBS of the STN does appear to affect inhibitory motor control, but the literature disagrees on whether STN DBS is detrimental or beneficial. When DBS is turned "on" response inhibition is worse compared with DBS "off", as assessed by the Stroop test (Witt et al 2004) and go/no-go tasks (Ballanger et al 2009;Hershey et al 2004). In the stop-signal task (SST), where the movement response must be halted during preparation or execution phases, some studies have shown that STN DBS enhances inhibitory control by shortening the SST reaction time of arm (Mirabella et al 2012) and finger (Swann et al 2011;van den Wildenberg et al 2006) movements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the models of cognitive control in WM discussed above (e.g., Braver and Cohen, 2000;Casey et al, 2002;Miller and Cohen, 2001), clinical studies have demonstrated inhibitory deficits in a range of conditions involving the loss of corticostriatal pathways through degeneration of the striatum (e.g., Aron et al, 2003b;Casey et al, 1997;Cools et al, 2003;Lawrence et al, 1998;Rosenberg et al, 1996;Rubia et al, 2001a). Studies of the effects of deep-brain stimulation, employed as a treatment for Parkinson's disease, have observed that stimulation of the subthalamic nucleus (STN) impairs performance on tasks requiring inhibition or attentional control, including GO/NOGO, Stroop, and WM tasks, possibly through disruption of output pathways through the striatum to PFC (Hershey et al, 2004;Jahanshahi et al, 2000).…”
Section: Item-specific Versus Process-specific Effects In Working Memorymentioning
confidence: 99%